Attention mechanisms and emotion judgment for Korean and American emotional faces: an eye movement study - Chunghee Chung; Sungmook Choi; Hyojin Jeong; Jiyeon Lee; Hyorim Lee (Frontiers in Psychology, 2023)
IntroductionThis study investigates attention mechanisms and the accuracy of emotion judgment among South Korean children by employing Korean and American faces in conjunction with eye-tracking technology.MethodsA total of 42 participants were individually presented with photos featuring either Korean or American children, and their task was to judge the emotions conveyed through the facial expressions in each photo. The participants’ eye movements during picture viewing were meticulously observed using an eye tracker.ResultsThe analysis of the emotion judgment task outcomes revealed that the accuracy scores for discerning emotions of joy, sadness, and anger in Korean emotional faces were found to be significantly higher than those for American children. Conversely, no significant difference in accuracy scores was observed for the recognition of fear emotion between Korean and American faces. Notably, the study also uncovered distinct patterns of fixation duration among children, depending on whether they were viewing Korean or American faces. These patterns predominantly manifested in the three main facial areas of interest, namely the eyes, nose, and mouth.DiscussionThe observed phenomena can be best understood within the framework of the “other-race effect.” Consequently, this prototype formation leads to heightened accuracy in recognizing and interpreting emotional expressions exhibited by faces belonging to the same racial group. The present study contributes to a deeper understanding of how attention mechanisms and other-race effects impact emotion judgment among South Korean children. The utilization of eye-tracking technology enhances the validity and precision of our findings, providing valuable insights for both theoretical models of face processing and practical applications in various fields such as psychology, education, and intercultural communication.